2015
DOI: 10.1007/s11255-015-1110-1
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Gleason Score ≥7 prostate cancer is an independent prognosticator for poor survival in nonmetastatic bladder cancer patients undergoing radical cystoprostatectomy

Abstract: Concomitant PCa in RCPx specimen of BCa patients is a common finding. The incidence of concomitant PCa has significantly increased within 2 decades, presenting a more aggressive phenotype. Age and in particular concomitant GS ≥7 PCa are independent prognosticators for poor survival in patients with nonmetastatic organ-confined BCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In a study in which whole-mount sectioning was performed, 36% of the specimens contained PCa [22]. Extensive pathological examination has likely become more common in Sweden during the study period, and we observed a slight increase of incidental PCa diagnoses over calendar time corroborating that a more extensive pathological examination increases the detection of PCa [4]. Currently, the proportion of men with latent PCa detected at autopsy is similar, that is around 30% in many Western countries, indicating that the same pool of undetected clinically insignificant PCa is detected at cystoprostatectomy as in autopsies of men who died of other causes than PCa [23].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In a study in which whole-mount sectioning was performed, 36% of the specimens contained PCa [22]. Extensive pathological examination has likely become more common in Sweden during the study period, and we observed a slight increase of incidental PCa diagnoses over calendar time corroborating that a more extensive pathological examination increases the detection of PCa [4]. Currently, the proportion of men with latent PCa detected at autopsy is similar, that is around 30% in many Western countries, indicating that the same pool of undetected clinically insignificant PCa is detected at cystoprostatectomy as in autopsies of men who died of other causes than PCa [23].…”
Section: Discussionsupporting
confidence: 73%
“…Similar proportions of incidental PCa at cystoprostatectomy have been reported in previous studies. In a systematic review and metaanalysis of 13,140 men, 24% men were diagnosed with PCa after cystectomy [2], and other studies that have reported similar proportions [3,4,5,22]. The type of pathological assessment of the prostate is likely to affect detection of PCa.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We present a case of non-muscle invasive urothelial cancer metastasised to the mandible and synchronous high-risk prostate cancer (PC). Incidental finding of PC in BC patients is generally clinically insignificant; however, there is some data to suggest that synchronous high-risk PC has poor survival prognosis for non-metastatic BC and treating PC improves the progression-free survival for BC 6 7. Our case highlights the importance of considering mandibular metastasis early in the differential when a patient presents with mental nerve neuropathy as well as treating synchronous PC that may affect overall survival.…”
Section: Introductionmentioning
confidence: 79%
“…PC is detected in 24%–51% of patients undergoing radical cystoprostatectomy for muscle invasive BC and up to 29% of these being high-risk PC 6. Incidentally diagnosed PC with Gleason score <6 does not affect overall survival of BC patients, but in a case series of 945 men with BC having radical cystoprostatectomy, Thomas et al found that synchronous high-risk PC with Gleason score of ≥7 and age >60 carried a poor survival prognosis for non-metastatic BC 7. The high concurrence of prostate and BC has led to theories of common carcinogenic pathway through mutations in tumour suppressor genes and effect of androgen receptor signalling involved in development and progression of both cancers 6…”
Section: Discussionmentioning
confidence: 99%